Long-term kidney complications in childhood leukemia survivors: a study from the Childhood and Adolescent Leukaemia (LEA) project - Carine Domenech; Paul Saultier; Zeinab Hamidou; Marie-Dominique Tabone; Marlène Pasquet; Virginie Gandemer; Stéphane Ducassou; Marilyne Poirée; Dominique Plantaz; Jean-Hugues Dalle; Pascal Chastagner; Sandrine Thouvenin; et al. (Haematologica)
Acute leukaemias represent the 1st cause of cancer in children. Their prognosis has improved significantly due to remarkable advances in therapeutic management, despite the risk of long-term consequences, especially for patients who underwent allogenic hematopoietic stem cell transplantation (aHSCT). Through the Leukaemia in Children and Adolescents (LEA) long-term follow-up cohort, we conducted a French national multicentre prospective study on the occurrence and risk factors of chronic kidney disease (CKD), differentiating glomerular and tubular dysfunctions, corresponding to the NephroLEA project.